Geodynamic evolution of the Minas Basin, southern São Francisco Craton (Brazil), during the early Paleoproterozoic: Climate or tectonic?. (August 2020) - Rossignol, Camille; Lana, Cristiano; Alkmim, Fernando
Abstract: Like many other cratons around the world, the São Francisco Craton is characterized by an early Paleoproterozoic (2.5–2.1 Ga) unconformity that is reported worldwide as the result of global glacial events leading to a major sea-level drop. To document the duration and the cause(s) of the stratigraphic hiatus in the São Francisco Craton, this study provides U–Pb dates obtained on detrital zircon grains from the Piracicaba Group, which directly overlies the unconformity. Our results show that this sedimentary unit is younger than 2333 ± 11 Ma and consequently deposited during the late Siderian or the early Rhaycian. This maximum depositional age demonstrates that the early Paleoproterozoic stratigraphic gap lasted for at least 60 Ma. Based on quantitative analyses of the age distribution of the Piracicaba Group, we evidence a major shift in sedimentary provenance between the sedimentary units located below and above the unconformity. This change is interpreted to be directly related to the development of a subduction system along the southern and eastern margins of the São Francisco proto-craton. Our results indicate that regional geodynamic events, and not only global glacial events and their consequences, must be accounted for in Earth system models for the early Paleoproterozoic. Graphical abstract: Image 1 Highlights: Late Siderian to Rhyacian age for the Piracicaba Group. Long lasting early Paleoproterozoic unconformity in the Minas Basin. Unconformity mainly induced by far-field tectonic stress.